Estimation Of Cumulative Effective Dose And Potential Risks Of Radiation Exposure From Multiple Scans Of Ct Head - Roslee, Mohd Amirul Azrie Mohd (2021)
In this study, the aims are to determine the cumulative individual organ dose and tissue absorbed dose received from multiple CT exposures, to analyse cumulative effective dose (ED) and estimate the risk of radiation induced cancer due to multiple CT exposures. A total of 323 patients (183 males and 140 females) underwent multiple CT head examinations (more than 3 exposures) at Advanced Medical and Dental Institute (AMDI) and Hospital Universiti Sains Malaysia (HUSM) were included in this study. Mostly patients were referred from Trauma and Neuro Departments of HUSM. Based on the study, lens organ dose consistently yields the highest values except for 13 times of multiple exposures; followed by thyroid’s dose (7.55 mSv) and lens (7.50 mSv). The highest organ dose was observed at lens (8.02 mSv). Based on International Commission on Radiological Protection (ICRP), the value was still below the level of radiation-induced cancer (100 mSv). However, mean absorbed dose for ≥ 3 times exposureexceeded the level of cataract formation stated by ICRP (0.5 Gy to 2 Gy for single exposure and 5 Gy for fractionated or protracted exposure). Both software calculation showed a positive correlation with number of exposures (r-value = 0.98). Besides, multiple CT exposures showed increment of the probability risk to induce cancer. Based on lifetime attributable risk (LAR) of incidence and mortality, the result showed that brain LAR was higher (53.87 and 50.17 per 100000 population) in female population compared to male population (21 and 17.45 per 100000 population) in 10 times multiple exposure. Increased exposures lead to significant increment of cancer risk with X2(7) = 76.89, p-value = 0.01(brain), X2(7) = 59.22, p-value = 0.01(salivary), with a mean value of 16.3 x 10-5 for LAR brain and 1.65 x 10-5 for salivary. The results also showed correlation of LAR incidence with mortality (r-value = 0.49 for brain and 0.42 for salivary). Thus, the repeated CT exposures should be minimized as to reduce the unnecessary radiation dose. The dose justification and optimisation of practice is crucial based on the concept of as low as reasonably practicable (ALARP).